Identifying risk factors for gallstones in postpartum women: A case–control study from a tertiary care setting of Peshawar - Azeem, Sheikh Muhammad Ibqar; Uzair, Muhammad; Afridi, Noor Sardar; Khan, Ayesha Ali; Khan, Tariq Hayat; Faryal Eid (International Journal of Pathology, 2025)
Background: Cholelithiasis is common in women of reproductive age, and the postpartum period is associated with physiological changes that may increase gallstone risk. This study aimed to identify factors associated with cholelithiasis in postpartum women. Methods: A case–control study was carried out from March 2024 to April 2025. One hundred and four postpartum women (52 ultrasonographically diagnosed cases of cholelithiasis and 52 controls with no gallstones) were recruited from Northwest General Hospital and Mercy Teaching Hospital. Demographic, obstetric, medical, lifestyle and biochemical data was collected using a structured proforma. Group comparisons used independent t-tests and chi-square tests; variables with p < 0.20 in univariate analysis were entered into multivariable logistic regression. Analyses were performed with SPSS v27. Results: Mean age was higher in cases than controls (p = 0.046). Mean BMI was greater in cases (0.001). Multiparity (p = 0.008), diabetes mellitus (p = 0.033), positive family history (p = 0.004), elevated ALP (p = 0.001) and total bilirubin (p < 0.001) were more frequent in cases. Sedentary lifestyle was significant on univariate analysis but not after adjustment. On multivariable analysis, independent predictors were higher (p = 0.003), multiparity (p = 0.029), diabetes (p = 0.049), positive family history (p = 0.022) and bilirubin (p = 0.001). Conclusion: In this postpartum study, metabolic (BMI, diabetes), obstetric (multiparity) and hereditary (family history) factors and raised bilirubin were independently associated with cholelithiasis. Targeted screening and preventive measures for high-risk postpartum women are warranted.